Peran Guru Dalam Menumbuhkan Apresiasi Sastra Melalui Pembacaan Puisi Di Kelas Rendah SDN Kesaud Kota Serang - Yoma Hatima (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to describe the role of teachers in fostering literary appreciation through poetry reading activities in the lower grades of Kesaud State Elementary School (SDN), Serang City. Literature, especially poetry, has great potential in shaping sensitivity, enriching vocabulary, and fostering children's imagination and empathy. However, literature learning at the elementary level is often still textual and less interesting for students. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with grade I and II teachers, and documentation of the learning process. The results of the study show that teachers act as facilitators, motivators, and models in expressing poetry expressively and enjoyably. Teachers who use communicative poetry reading methods, such as rhythmic reading, body movements, and facial expressions, have been shown to be able to attract students' attention and increase their interest in literature. In addition, student involvement in rereading favorite poems is also an effective strategy in fostering a love for literary works. This study recommends the importance of teacher training in creative poetry reading techniques and the provision of relevant and interesting children's literature teaching materials. Thus, literary appreciation among elementary school students can be instilled early on through a fun and meaningful approach